2004
DOI: 10.4315/0362-028x-67.4.799
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Three Methods for the Isolation of Arcobacter spp. from Retail Raw Poultry in Northern Ireland

Abstract: Recent evidence suggests that arcobacters, especially Arcobacter butzleri, are potential foodborne pathogens, but standardized detection methods have yet to be established. A study was undertaken to determine which of three isolation methods was the most effective for the isolation of Arcobacter spp. from fresh raw poultry. Methods 1 was microaerobic and involved a membrane filtration step followed by plating onto blood agar. Method 2 was also microaerobic and involved enrichment and plating media containing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…A. cryaerophilus and A. skirowii are slow growing species and may need more than 72 h to produce visible colonies on the agar plates; thus, with longer incubation period which in some studies up to 8 days incubation (Atabay, Wainø, & Madsen, 2006;Aydin, Gümüssoy, Atabay, Ica, & Abay, 2006), it may be possible to isolate these and other species of Arcobacter. The use of more than one isolation method is also recommended as this would allow for maximum recovery of arcobacters from naturally contaminated chicken meat (Scullion, Harrington, & Madden, 2004). Another possible explanation could be that A. cryaerophilus may not compete well with A. butzleri during enrichment as suggested by Houf, De Zutter, Van Hoof, and Vandamme (2002) who had isolated only A. butzleri from neck skin samples after enrichment but were able to isolate both A. cryaerophilus and A. butzleri by direct plating.…”
Section: Discussionmentioning
confidence: 92%
“…A. cryaerophilus and A. skirowii are slow growing species and may need more than 72 h to produce visible colonies on the agar plates; thus, with longer incubation period which in some studies up to 8 days incubation (Atabay, Wainø, & Madsen, 2006;Aydin, Gümüssoy, Atabay, Ica, & Abay, 2006), it may be possible to isolate these and other species of Arcobacter. The use of more than one isolation method is also recommended as this would allow for maximum recovery of arcobacters from naturally contaminated chicken meat (Scullion, Harrington, & Madden, 2004). Another possible explanation could be that A. cryaerophilus may not compete well with A. butzleri during enrichment as suggested by Houf, De Zutter, Van Hoof, and Vandamme (2002) who had isolated only A. butzleri from neck skin samples after enrichment but were able to isolate both A. cryaerophilus and A. butzleri by direct plating.…”
Section: Discussionmentioning
confidence: 92%
“…Previous reports have described protocols to estimate Arcobacter prevalence in live birds or poultry meat (DeBoer et al 1996;Eifert et al 2003;Houf et al 2001;Johnson et al 1991;Lerner et al 1994;Phillips 2001;Ridsdale et al 1998;Scullion et al 2004;Son et al 2006). Because of its complexity, few studies have evaluated Ellinghausen-…”
Section: Introductionmentioning
confidence: 98%
“…The serogroup identity of A. butzleri isolates from poultry and clinical cases of diarrhoeal illness suggested that poultry are possible reservoir of infection (Marinescu et al 1996). Poultry, including up to 97% of chicken carcasses (Atabay et al 2003;DeBoer et al 1996;Kabeya et al 2003;Lammerding et al 1996), retail products (Scullion et al 2006), and up to 80% of ground poultry (Manke et al 1998;Rivas et al 2004;Scullion et al 2004) are often contaminated with Arcobacter spp., primarily A. butzleri. In one study, A. cryaerophilus was the only Arcobacter species recovered from poultry transport crates (Houf et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been reported that the enrichment step reduces the diversity of Arcobacter species recovered in the plating medium in comparison with direct plating (68,71). In summary, it can be said that the methods for recovering Arcobacter are very diverse (Table 4) and that there is a lack of consensus about which of them is the most useful (depending on the type of sample), because few comparative studies have been performed (6,85,134) and, to our knowledge, there is no study in which they were all compared simultaneously. Some of the recovery problems reported include the inhibition of some Arcobacter species when using certain antibiotics (11,72) and insufficient inhibition of the accompanying microbiota (6,44).…”
mentioning
confidence: 98%